A new species of the genus Corimalia Gozis, 1885 (Coleoptera: Brentidae: Nanophyinae) from the Caucasus - Schön, Karel; Skuhrovec, Jiří (Zootaxa, 2016)
Corimalia strejceki Schön& Skuhrovec,sp. nov. is described and illustrated from the Caucasus, Russia. The new species is compared with the allopatric C. aliena (Faust, 1890) differing in size, shape of scales, scale patch close to the scutellum, size of mucrones on the meso- and metatibiae, and also shape of the apex of the penis. Controversy over the number of segments in the antennae in the genus Corimalia is summarized. An annotated catalogue and key of all Corimaliini species in the Caucasus is provided.
Keywords: Animals; velikost těla; brouci; anatomické struktury zvířat; Animal Structures; zvířata; mužské pohlaví; Body Size; velikost orgánu; Female; Male; Coleoptera; Organ Size; rozšíření zvířat; Animal Distribution; Russia; ženské pohlaví; Rusko